Investigating the Attitudes and Views of the Librarians and Faculty members of Shiraz University over deploying Wi-Fi in Academic Libraries - Jafar Mehrad (Iranian Journal of Information Processing & Management, 2009)
Given the importance and wide scope of Wi-Fi applications within academic environs in developed countries and its use in library services, its utilization within academic libraries in Iran is felt. While presenting Wi-Fi networks, the present study employed a survey of librarians and faculty members in Shiraz University to investigate their the outlook and viewpoints regarding the deployment of such networks in academic libraries. Findings demonstrated that librarians are very inclined to use Wi-Fi in library services such as listing, shelf-reading and OPAC and demand comprehensive network coverage throughout the entire library spaces. Meanwhile, faculty members expressed the necessity of increasing use of such networks all over the campus and remote access to library resources. Generally given the outcome of the present investigation, although Wi-Fi application in libraries is a novel and emerging phenomenon yet to catch on in Iran, librarians, researchers and professors are very keen about its use and application within academic environments.